(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
During 1997-1998 samples of leaves of Celtis australis L., Ulmus sp. and of Viburnus tinus L. respectively infested from Phyllonorycter millierella Stgr., Ph. corylifoliella Hbn. and Stigmella sp., Ph. lanthanella Schk. were collected, in order to investigate on their indigenous antagonists. The following parasitoids emerged from Ph. lanthanella: Cirrospilus lyncus Walker, Pediobius saulius (Wlk.), two unidentified species of Braconids, and two species of Eulophids belonging to Sympiesis Forster Cladosympiesis-group; from Ph. corylifoliella: Pholetesor circumscriptus (Nees) Cirrospilus sp., C. diallus (Wlk.), C. lyncus, C. pictus (Nees), C. viticola Rondani, P. saulius, Pnigalio agraules (Walker), Ratzeburgiola incompleta Boucek, one of the two upmentioned species of Cladosympiesis-group, as well as an Eulophid wasp belonging to Tetrastichinae. With respect to R. incompleta it is the first record from this host. From Stigmella sp.: Apotetrastichus postmarginalis (Boucek) and another three not yet identified Eulophid species; from Ph. millierella: Ph. circumscriptus, Pnigalio agraules (Walker) an Eulophid of Cladosympiesis-group, as well as Cirrospilus sp. and P. saulius. lt must be pointed out that A. postmarginalis, C. diallus, C. pictus, P. agraules as Phyllocnistis citrella Stainton parasitoids are recorded in the literature.